PI3K/Akt and HIF-1 signaling pathway in hypoxia-ischemia - Zhang, Zhen (Mol Med Rep, 2018)
Hypoxia-ischemia (H-I) is frequently observed in perinatal asphyxia and other diseases. It can lead to serious cardiac injury, cerebral damage, neurological disability and mortality. Previous studies have demonstrated that the phosphatidylinositol-3 kinase (PI3K)/protein kinase B (Akt) signaling pathway, which regulates a wide range of cellular functions, is involved in the resistance response to H-I through the activation of proteins associated with survival and inactivation of apoptosis-associated proteins. It can also regulate the expression of hypoxia-induced factor-1α (HIF-1α). HIF-1α can further regulate the expression of downstream proteins involved in glucose metabolism and angiogenesis, such as vascular endothelial growth factor and erythropoietin, to facilitate ischemic adaptation. Notably, HIF-1α may also induce detrimental effects. The effects of HIF-1 on ischemic outcomes may be dependent on the H-I duration, animal age and species. Thus, further investigation of the PI3K/Akt signaling pathway may provide further insights of the potential targets for treating diseases accompanied by H-I.